CAMPUR KODE BAHASA INDONESIA PADA TUTURAN BERBAHASA JAWA DALAM FILM KARTINI KARYA HANUNG BRAMANTYO - Ade Rahima; Nadya April Tayana (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this research is to describe "Indonesian language code-mixing in the Javanese utterance of Kartini film by Hanung Bramantyo". In this film, there are many types of code-mixing occured, namely: code-mixing of words, code-mixing of frase, and code-mixing of clause. In addition, the film also included code-mixing characteristics based on informal situation. The primary data in this research is phrases and words, whereas, secondary data is a transcription dialogue in the Kartini film by Hanung Bramantyo. This research is qualitative research by using descriptive methods. In analyzing the data, Nababan’s theory is used. Moreover, Chaer and Agustina’s theories are used in analyzing code-mixing. Based on the results of data analysis, it can be concluded that the results of this study include 1) code-mxing of the words kita, aku, and, masuk. Meanwhile the code-mixing of frase can be seen from the words sejak semua and menemukan kebebasanmu and code-mixing of clause can be seen from aku nulis iklan. 2) The characteristic of code-mixing based-situation is the informal situation.